Vegetation Characteristics and Volume Estimation of Shorea and Schima-castanopsis of Kaski District of Nepal - Baul, Tarit Kumar; Charlery, Lindy Callen; Suber, Marta; Hardial, Urmilla; Muller, Michael (Indian Forester, 2013)
This study aims to evaluate the quantity and quality of resources available in the study area, as well as understanding the silvicultural practices, assessing the risks and its impact on trees and recommendations for a better, more 3 sustainable management. Considering timber trees, Shorea accounts as 40.943m /ha in the Shorea forest where as Schima wallichii as 71.33m3/ha in the Schima-Castanopsis forest stand. The mean total volume of poles is 194.92m3/ha for Shorea in the Shorea stand while the volume of Castanopsis indica is 153.08m3/ha and 49.90 m 3/ha for S. wallichii in the Schima-Castanopsis forest stand. In Shorea stand, enormous number of regeneration of Shorea and S. wallichii was found, where as in Schima-Castanopsis forest, C. indica and S. wallichii showed poor regeneration. The Schima-Castanopsis stand was found to be more diverse with compared to that of Shorea forest. There are five (5) fire lines which are cleaned and kept free of litter all the year long. There was no serious occurrence of insect risk. Maintenance of old, poor quality trees, on forest floor is necessary to gear up the growth of younger promising.